2021
DOI: 10.1186/s12935-021-02164-8
|View full text |Cite
|
Sign up to set email alerts
|

The plasma exosomal miR-1180-3p serves as a novel potential diagnostic marker for cutaneous melanoma

Abstract: Background Exosomes are a promising tool in disease detection because they are noninvasive, cost-effective, sensitive and stable in body fluids. MicroRNAs (miRNAs) are the main exosomal component and participate in tumor development. However, the exosomal miRNA profile among Asian melanoma patients remains unclear. Methods Exosomal miRNAs from the plasma of melanoma patients (n = 20) and healthy individuals (n = 20) were isolated and subjected to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…So far, the number of studies on EV embedded miRNAs of melanomas as biomarkers is limited. miR-1180-3p was reported as potential exosomal diagnostic marker, but in contrast to the miRNAs reported here, this miRNA was shown to be reduced in melanoma patients ( 72 ). The miR-222 was proposed as a diagnostic marker in melanoma, but it has not been analysed in patient-derived EVs, but only in cell lines derived from patients ( 82 ).…”
Section: Discussioncontrasting
confidence: 98%
“…So far, the number of studies on EV embedded miRNAs of melanomas as biomarkers is limited. miR-1180-3p was reported as potential exosomal diagnostic marker, but in contrast to the miRNAs reported here, this miRNA was shown to be reduced in melanoma patients ( 72 ). The miR-222 was proposed as a diagnostic marker in melanoma, but it has not been analysed in patient-derived EVs, but only in cell lines derived from patients ( 82 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Using ROC curve analysis of expression level in blood samples, miR-1180-3p was verified to owning the discriminating ability between CRC and healthy participants. In previous studies, miR-1180-3p has showed its diagnostic value in melanoma, gastric cancer, and early hepatocellular carcinoma [ 21 , 30 , 31 ]. This finding would shed light on the development of miR-1180-3p as a new noninvasive diagnostic marker for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-145-5p could inhibit PLD5 resulting in downregulation of cell proliferation and metastasis in prostate cancer [ 36 ]. miR-1180-3p has been reported involving in the regulation of C11of54 in hepatocellular carcinoma and ST3GAL4 in cutaneous melanoma [ 30 , 37 ]. The search for gene targets of miR-1180-3p rendered COL12A1 by three online databases.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in another study, EMT regulators miR-191 and let-7a were significantly higher in serum-derived sEVs of stage I melanoma patients compared to control patients in a cohort of 41 patients (20 nonmelanoma vs. 21 stage I melanoma) [121]. In a more recent study, RNA-seq of plasma-derived sEVs from a patient cohort of 20 patients per group (melanoma vs. healthy control patients) and a validation cohort of 28 patients per group revealed miR-1180-3p as a novel potential diagnostic marker for cutaneous melanoma [122] with an area under the curve (AUC) value of 0.729. In functional experiments, miR-1180-3p reduced proliferation, migration, and invasion of melanoma cells and was negatively regulated by ST3GAL4 [122].…”
Section: Ev-derived Mirna Profiling Of Melanoma Liquid Biopsiesmentioning
confidence: 98%
“…In a more recent study, RNA-seq of plasma-derived sEVs from a patient cohort of 20 patients per group (melanoma vs. healthy control patients) and a validation cohort of 28 patients per group revealed miR-1180-3p as a novel potential diagnostic marker for cutaneous melanoma [122] with an area under the curve (AUC) value of 0.729. In functional experiments, miR-1180-3p reduced proliferation, migration, and invasion of melanoma cells and was negatively regulated by ST3GAL4 [122]. A further study revealed a potential homeostatic role of sEVs in regulating miR-494.…”
Section: Ev-derived Mirna Profiling Of Melanoma Liquid Biopsiesmentioning
confidence: 99%